Green, Multi‐Gram One‐Step Synthesis of Core–Shell Nanocomposites in Water and Their Catalytic Application to Chemoselective Hydrogenations. Issue 50 (27th October 2016) - Urayama, Teppei; Mitsudome, Takato; Maeno, Zen; Mizugaki, Tomoo; Jitsukawa, Koichiro; Kaneda, Kiyotomi
Abstract: We devise a new and green route for the multi‐gram synthesis of core–shell nanoparticles (NPs) in one step under organic‐free and pH‐neutral conditions. Simply mixing core and shell metal precursors in the presence of solid metal oxides in water allowed for the facile fabrication of small CeO2 ‐covered Au and Ag nanoparticles dispersed on metal oxides in one step. The CeO2 ‐covered Au nanoparticles acted as a highly efficient and reusable catalyst for a series of chemoselective hydrogenations, while retaining C=C bonds in diverse substrates. Consequently, higher environmental compatibility and more efficient energy savings were achieved across the entire process, including catalyst preparation, reaction, separation, and reuse. Abstract : The simpler the better : Core–shell nanocomposites were successfully synthesized in one step in multi‐gram scale under organic‐free and pH‐neutral conditions. The synthesized core–shell nanoparticles showed high chemoselectivity in a series of hydrogenations without any additives, while retaining C=C bonds in diverse substrates.